Allergen-Induced Asthma - Donald W Cockcroft (Canadian Respiratory Journal)
It was only in the late 19th century that specific allergens, pollen, animal antigens and, later, house dust mite, were identified to cause upper and lower airway disease. Early allergen challenge studies, crudely monitored before measurement of forced expiratory volume in 1 s became widespread in the 1950s, focused on the immediate effects but noted in passing prolonged and/or recurrent asthma symptoms. The late asthmatic response, recurrent bronchoconstriction after spontaneous resolution of the early responses occurring 3 h to 8 h or more postchallenge, has been identified and well characterized over the past 50 years. The associated allergen-induced airway hyper-responsiveness (1977) and allergen-induced airway inflammation (1985) indicate that these late sequelae are important in the mechanism of allergen-induced asthma. Allergens are now recognized to be the most important cause of asthma. A standardized allergen inhalation challenge model has been developed and is proving to be a valuable research tool in the investigation of asthma pathophysiology and of potential new pharmacological agents for the treatment of asthma.